2023
DOI: 10.7759/cureus.44364
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Predictive Factors for Return to Sports in Female Athletes With Stress Urinary Incontinence

Nobuo Okui,
Tamer Erel,
Machiko Aurora Okui

Abstract: Introduction This study aimed to identify predictive factors for successful return to sports among elite female athletes (EFAs) experiencing stress urinary incontinence (SUI). We used machine learning to analyze these predictors. Methods This study was conducted at Yokosuka Urogynecology and Urology Clinic, located in Yokosuka City, Kanagawa, Japan. A total of 153 EFAs with postpartum SUI were included in this retrospective cohort study. Information regarding the frequency of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Both VEL and UEL were well tolerated in our study, with no reported complaints from the patients, such as burning during urination or dysuria. Furthermore, there were no observed indications of a risk of urethral stricture associated with laser therapy, which is consistent with previous research [8][9][10][11][12][13][14]19,20].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Both VEL and UEL were well tolerated in our study, with no reported complaints from the patients, such as burning during urination or dysuria. Furthermore, there were no observed indications of a risk of urethral stricture associated with laser therapy, which is consistent with previous research [8][9][10][11][12][13][14]19,20].…”
Section: Discussionsupporting
confidence: 91%
“…Our selection consisted of the non-ablative erbium:yttrium-aluminum-garnet (Er:YAG) SMOOTH® laser, accompanied by a laser tailored for the vagina (vaginal erbium laser (VEL)) and the urethra (urethra erbium laser (UEL)). Previous reports showed that a combination of VEL and UEL improved severe SUI [8][9][10][11][12][13][14]. VEL itself is very 1 2 safe, with few side effects observed [12,14].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This study aimed to develop a graph theory-based navigation system using data from previous research, focusing on the treatment choices for Stress Urinary Incontinence (SUI). SUI affects a significant proportion of women, significantly diminishing their quality of life 7 10 . A common treatment is mid-urethral sling (MUS) procedures using polypropylene mesh, but this method can lead to postoperative pain, foreign body reactions, inflammation, and even the emergence or worsening of Urgency Urinary Incontinence (UUI) 11 13 .…”
Section: Introductionmentioning
confidence: 99%